IMPLEMENTASI CONVENTION ON THE ELIMINATION OF ALL FORMS OF DISCRIMINATION AGAINST WOMEN (CEDAW) DALAM WOMENOMICS TERHADAP PELUANG KERJA PEREMPUAN DI JEPANG - Ramadhani, Ilga; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
Women in Japan continue to face inequalities in the employment sector, particularly in job access, wage gaps, employment quality, and career advancement opportunities. Although Japan ratified the Convention on the Elimination of All Forms of Discrimination Against Women or CEDAW in 1985, the implementation of gender equality principles in domestic policies still faces structural and cultural barriers. Womenomics, introduced under the administration of Prime Minister Shinzo Abe, became one of Japan’s efforts to increase women’s participation in the labor market while responding to national economic challenges caused by population decline and labor shortages. This study employs a constructivist perspective, international regime theory, and the nation-state level of analysis using a qualitative-descriptive method through library research. The focus of this research is the implementation of Article 11 of CEDAW in Womenomics policy toward women’s employment opportunities in Japan during the 2018-2020 period. The findings indicate that Womenomics contributed to increasing women’s labor participation and strengthening gender equality policy support. However, its implementation has not fully achieved substantive equality, as the gender wage gap remains high, women are still concentrated in non-regular employment, female representation in leadership positions remains limited, and patriarchal culture as well as traditional social norms continue to influence Japan’s labor market. Keywords: CEDAW, Womenomics, women’s employment opportunities, gender equality, Japan.